Exploring the Intersection of Cognitive Therapy and Education - Katie Archer Olson (Journal of Scholarly Engagement)
Education faculty and pre-service teachers face the nearly impossible task of preparing learners for today's world. Beyond personal limitations of not being omniscient or knowing all the strategies that create strong lifelong learners, they are bombarded with mandates from accreditation, political bodies, and the state, creating gaps in pertinent strategies to support struggling learners. A major car accident of an instructor forces a critical look at possible contributions to these gaps after undergoing cognitive therapy due to a traumatic brain injury and intimately learning about the memory process. The article highlights how Greenberger's new guide for reflective practice helps the scholar-practitioner by developing working ideas, generating a reflective narrative based on personal experiences during cognitive therapy, navigating an evaluation of ideas backed by peer-reviewed literature, and providing practical solutions to bridge the gap in faculty and pre-service teachers' knowledge of the memory process. The process underscores the transformative potential of proactively incorporating reflective practice to help faculty develop resources to improve teaching practices to support diverse struggling learners. Keywords: memory process, education, reflection, struggling learners, teacher preparation